A Twenty-year Review of Early and Late-presenting Congenital Bochdalek Diaphragmatic Hernia: Are They Different Clinical Spectra? - Szu-Wen Chang; Hung-Chang Lee; Chun-Yan Yeung; Wai-Tao Chan; Chyong-Hsin Hsu; Hsin-An Kao; Han-Yang Hung; Jui-Hsing Chang; Jin-Cherng Sheu; Nein-Lu Wang (Pediatrics and Neonatology)
Congenital Bochdalek diaphragmatic hernia (CDH) is easily recognized if it is present shortly after birth. However, cases of delayed CDH presentation are more subtle and therefore less easily diagnosed. Methods: We retrospectively analyzed 85 patients who were under 18 and diagnosed with CDH between June 1987 and May 2007. Those diagnosed before 1 month of age were categorized as having early-presenting CDH and those diagnosed after 1 month were categorized as having late-presenting CDH. Results: Of the 85 cases, 68 (80%) were early-presenting and 17 (20%) were late-presenting CDH. Respiratory symptoms were more common in early-presenting CDH, while gastrointestinal complaints were more dominant in the late-presenting group, particularly in patients with left diaphragmatic defects. Late-presenting CDH, which was more likely to be associated with chronic gastrointestinal symptoms, was associated with a lower mortality than acute early-presenting CDH with respiratory symptoms, despite the more prompt diagnosis of the latter. The small bowel was the organ most commonly herniated into the thorax. Congenital heart disease was the most commonly associated malformation, but the presence of associated anomalies did not increase mortality. Conclusion: Early-presenting CDH shows acute symptoms, is readily diagnosed, and requires prompt intervention to prevent death. In contrast, late-presenting CDH shows more subtle symptoms and is more difficult to diagnose. Although the late-presenting CHD has better prognosis, it still requires surgery intervention to alleviate the symptoms. Clinicians must maintain a high index of suspicion for CDH, regardless of its presentation.